Mixed methods analysis of factors influencing change in clinical behaviours of non‐physician anaesthetists in Kenya following obstetric anaesthesia training. (20th May 2020) - Lilaonitkul, M.; Mishra, S.; Pritchard, N.; Andhoga, J.; Olang', P.; Kibet, E. B.; Walker, I. A.; Hart, J.; Byrne‐Davis, L.
Summary: Maternal mortality rates in low‐middle income countries remain high, with sub‐Saharan Africa accounting for two‐thirds of global maternal deaths. Inadequate staff training is one of the main contributors to anaesthesia‐related deaths and the Association of Anaesthetists developed the Safe Anaesthesia from Education course in collaboration with the World Federation of Societies of Anaesthesiologists to address this training gap. We aimed to evaluate the impact of this course among Kenyan participants. Mixed methodologies and secondary analyses of anonymised data were used to study translation of learning into practice. In total, 103 participants from 66 facilities who attended courses between 2016 and 2017 were analysed. Ninety (87%) participants who were followed up completed knowledge tests. Baseline median (IQR [range]) knowledge test score was 41 (37–43 [21–46]). There was a significant improvement in median (IQR [range]) knowledge test score immediately post‐course (43 (41–45 [33–48]); p < 0.001) which was sustained at 3–6 month follow‐up (43 (41–45 [32–50]); p < 0.001 compared with baseline). Eighty‐four of the 103 participants were observed in their workplace and capability, opportunity and motivation‐behaviour framework was used to study the barriers and facilitators to practice change. Psychological capability and reflective motivation were the main factors enabling positive behaviour change such as team communication and pre‐operative assessment, whereas physical and social opportunity accounted for the main barriers to behaviours such as performing the surgical safety checklist. Our study demonstrates that the Safe Anaesthesia from Education obstetric course is relevant in the low‐resource setting and may lead to knowledge translation in clinical practice.